Political ecology of forest trees in the Philippines - Fernandez, Pepito R., Jr (Danyag : Journal of Humanities and Social Sciences, 1997)
Behind obvious processes explaining deforestation in the Philippines lies a variety of important factors which go back to colonial times and include state elitism, corruption and the nature of the global economy. The interaction of these three major forces has, in turn, resulted in specific explanatory factors in the deforestation process. Demystifying the issue of deforestation in the Philippines can help state, market and societal forces move towards ecologically sound and equitable use of upland resources.